In situ and Multi-Substrate Detection of Elastase Enzymatic Activity External to Microdialysis Sampling Probes using LC-ESI-MS - Wang, Ying (Anal Chem, 2008)
Extracellular proteases play significant roles in mammalian development and disease. Enzymatic activity external to a microdialysis sampling probe can be determined by infusing judicious choices of substrates followed by collecting and measuring the products. Porcine pancreatic elastase was used as a model enzyme with two substrates possessing different cleavage sites, N-methoxysuccinyl-Ala-Ala-Pro-Val-7-amino-4-methylcoumarin (FL-substrate) and N-Succinyl-Ala-Ala-Ala-p-nitroanilide (UV-substrate). These substrates were infused through the microdialysis sampling probe to a solution containing elastase. The resulting four products and the remaining two substrates were collected into the dialysate and were subsequently analyzed offline using LC-MS with electrospray ionization. All analytes were identified using extracted ion chromatograms of m/z 628 (FL-substrate); m/z 452 (UV-substrate); m/z 471 (N-methoxysuccinyl-Ala-Ala-Pro-Val, FL-NTP); m/z 332 (N-Succinyl-Ala-Ala-Ala, UV-NTP); m/z 176 (7-amino-4-methylcoumarin, AMC) and m/z 139 (p-nitroaniline, pNA). FL-NTP and FL-substrate exhibited 10-fold higher ion production as compared to AMC with equimolar standards. Microdialysis sampling combined with LC-ESI-MS detection allowed for in situ determination of the enzymatic activity of a protease external to the microdialysis probe when using different peptide-based substrates.